Antioxidant Contributors in Seed, Seed Coat, and Cotyledon of γ-ray-Induced Soybean Mutant Lines with Different Seed Coat Colors - You Jin Lim; Soon-Jae Kwon; Shanshan Qu; Dong-Gun Kim; Seok Hyun Eom (MDPI AG, 2021)
The development of soybean with high antioxidant activities for use in the food and cosmetics industries is a target of breeding programs. In soybean, antioxidants are associated with seed color, although the metabolic basis for seed coloration remains incompletely understood. We selected six γ-ray-induced mutant lines that exhibited black, partially black, brown, partially brown, or yellowish-white pigmentation in the seed coat. Antioxidant activity and contents of anthocyanins, flavan-3-ols, and isoflavones were evaluated in the seed coat and cotyledons. The lines with black or brown seeds showed the highest antioxidant activities. The cotyledons showed no significant differences in seed coat components or antioxidant activities among lines. Black and brown seed coat components showed the highest antioxidant activities. The black seed coat contained five anthocyanins, whereas seed coats of brown- and yellow-seeded lines entirely lacked anthocyanins. Both black and brown seeds were rich in flavan-3-ols, including catechin and epicatechin, which were the predominant antioxidant contributors in brown seeds. Isoflavone contents showed weaker correlations with antioxidant activity than anthocyanins and flavan-3-ols. These results demonstrated that antioxidant activities were determined by anthocyanins in black seeds and flavan-3-ols in brown and black seeds, whereas relatively low antioxidant activities in yellow seeds reflected their high isoflavone contents.